Are determinants of rural and urban food security and nutritional status different?: some insights from Mozambique - Garrett, James L.; Ruel, Marie T. (International Food Policy Research Institute, 1999)
Undernutrition of children 0-60 months old in Mozambique is much higher in rural than in urban areas. Food security is about the same, although substantial regional differences exist. Given these outcomes, we hypothesized that the determinants of food security and nutritional status in rural and urban areas of Mozambique would differ as well. Yet we find that the determinants of food insecurity and malnutrition, and the magnitudes of their effects, are very nearly the same. The difference in observed outcomes appears primarily due to differences in the levels of critical determinants rather than in the nature of the determinants themselves.